Manufacturing FDI in Sub-Saharan Africa : Trends, Determinants, and Impacts - Chen, Guangzhe; Geiger, Michael; Fu, Minghui (World Bank Group, Washington, DC, 2015)
This report offers five policy recommendations that could contribute to the attraction of manufacturing FDI in Africa. To further the benefits of FDI, especially in the manufacturing sector, policymakers in Africa should: First, manage FDI flows and FDI-related policies in a way that maximizes spillovers in host countries. Second, realize the emergence of FDI from newpartners, especially in manufacturing FDI, and establish platforms that help in the attraction ofnew FDI. Third, increase investment on key infrastructure to overcome constraints for manufacturing activities to develop, especially in power supply and transportation and logistics services. Fourth, take better advantage of the currently dominating market-seeking manufacturing FDI to improve the weak industry base in the shortterm. Market-seeking FDI has a sizeable positivecontribution to the host economy. Fifth, strengthen the linkages between domestic material input and foreign manufacturing investment.